ELECTROPHORETIC ANALYSIS OF 11 ENZYMES IN NATURAL POPULATIONS OFROOT, 1926 (DIPTERA: CULICIDAE) IN THE AMAZON REGION - Santos, Jaselita M.m. Dos; Tadei, Wanderli Pedro [UNESP]; Contel, Eucléia P.b (Instituto Nacional de Pesquisas da Amazônia, 1996)
Of eleven proteins analyzed in four Amazonian populations, the esterases showed the greatest variation, with five activity zones. EST1, EST2 and EST5 showed variation in each of the populations studied. EST1 and EST2 are each controlled by two, and EST5 by four, codomi-nant alleles. LAP presented six activity zones, with codominant variation in LAP5and LAP6.oc—GPDH was monomorphic with one activity band on starch gel and two on polyacrylamide gel. 1DH presented two activity zones, with variation in the IDHl region. PGM had a single activity zone, with variation in all populations. The Ariquemes populations showed five alleles and the other populations three, all of then codominant. Three activity zones with two codominant alleles were observed for ODH. Aldehyde Oxidase showed two activity zones, with variation in AOl only in the Ariquemes and Porto Velho/Samuel populations. 6-PGDH showed only one activity zone and variation only in the Ariquemes population. The remaing systems - XDH, G-6-PDH and GDH. was monomorphic.

Dos 11 sistemas protéicos analisados, em quatro populações da Amazônia, as esterases foram as que apresentaram maior variação, com cinco zonas de atividade. EST1, EST2, e EST5 mostraram variação genética determinada em todas populações estudadas, sendo que as duas primeiras são resultantes do controle de dois alelos e a EST5 de quatro, todos codominantes. A LAP consiste de seis zonas de atividade e com variação apenas nos loci LAP5e LAP6,ambos codominantes. A GPDH mostrou-se monomórfica com uma zona de atividade em gel de amido e duas em poliacrilamida. A IDH apresentou duas zonas de atividade, com variação na região da IDH1. A PGM consiste de uma única zona de atividade e com variação em todas as populações estudadas. A população de Ariquemes revelou cinco alelos e as demais três, todos codominantes. Para a ODH, foram observadas três zonas de atividade com dois alelos codominantes. A enzima AO apresentou duas zonas de atividade, sendo que a AOl mostrou-se variável apenas em Ariquemes e Porto Velho/Samuel. 6-PGDH possui apenas uma zona de atividade e variação apenas em Ariquemes. Os demais sistemas - XDH, G-6-PDH e GDH - mostraram-se monomórficos.
Análise Eletroforética de 11 Enzimas era Populações Naturais de Anopheles (Ν.) darlingi Root, 1926 (Diptera: Cuiicidae) na Região Amazônica
Keywords: Anopheles darlingi; isozymes; electrophoresis; Anopheles darlingi; isoenzimas; eletroforese